STRAIN-RATE AND PRINTING DIRECTION DEPENDENCY OF COMPRESSIVE BEHAVIOUR OF 3D PRINTED STAINLESS STEEL 316L - Michaela Neuhäuserová; Petr Koudelka; Jan Falta; Marcel Adorna; Tomáš Fíla; Petr Zlámal (Acta Polytechnica CTU Proceedings)
The paper is focused on evaluation of the relation between mechanical properties of 3D printed stainless steel 316L-0407 and printing direction (i.e. the orientation of the part which is being printed in the manufacturing device) subjected to compressive loading at diﬀerent strain-rates. In order to evaluate the strain rate dependency of the 3D printed material’s compressive characteristics, dynamic and quasi-static experiments were performed. Three sets of bulk specimens were produced, each having a diﬀerent printing orientation with respect to the powder bed plane (vertical, horizontal and tilted). To assess the deformation behaviour of the 3D printed material, compressive stress-strain diagrams and compressive yield strength and tangent modulus were evaluated.